Odpowiedzi

Najlepsza Odpowiedź!
2009-11-23T13:12:56+01:00
1-2sin²α=2cos²α-1
2=2(sin²α+cos²α)
2=2, tożsamość α∈R

(2/cos²α)-1= 1+2 tg²α / *cos²α ≠0
2-cos²α=cos²α+2sin²α
2=2(sin²α+cos²α)
2=2, tożsamość

cosα≠0
α≠(2k+1)(π/2) dla k∈C
2 1 2
2009-11-23T13:14:51+01:00
A)
1 -2sin²α = 2cos²α -1
Korzystamy z jedynki trygonometrycznej
sin²α + cos²α = 1 ----> sin²α = 1 -cos²α
Mamy
1 - 2sin²α = 1 - 2*(1 -cos²α) = 1 - 2 + 2cos²α = 2cos²α -1
ckd.
b)
[2/(cos²α)] -1 = 1 + 2 tg²α

{[ 2*(sin²α + cos²α] - cos²α}/ cos²α = [2*sin²α + cos²α]/cos²α =
= 2*sin²α/cos²α + cos²α/cos²α = 1 + 2* tg²α,
bo
sinα/cosα = tg α, a sin²α/ cos²α = tg²α
ckd.
α nie może się równać 90 stopni +k*180 stopni, bo wtedy
cosα = 0, a nie można dzielić przez 0.
3 3 3